Relational and Sexual Experiences of Betrayal From the Point of View of Sexually Victimized Young Women - Guyon, Roxanne (Journal of interpersonal violence, 2021)
Worldwide, it is estimated that one in five women have reported being sexually victimized before the age of 18. Girls are particularly at risk of sexual abuse at the end of adolescence and are more vulnerable to revictimization during this period. However, there is a paucity of findings related to the relational and sexual impacts of child sexual abuse among young women. The traumagenic dynamics model, proposed by Finkelhor and Browne, postulates that the consequences of sexual abuse can be analyzed in light of four distinct dynamics: traumatic sexualization, betrayal, powerlessness, and stigmatization. Among the four postulated dynamics, betrayal appears to be a key element to gain insight on the relational challenges experienced by victims, as betrayal situations can recur in romantic relationships. The present study aimed to describe, from the point of view of young women victims of child sexual abuse, the issues related to betrayals in their relational and sexual experiences. Semi-structured interviews were conducted with 19 young women aged 18 to 25 years old who had reported sexual victimization. Two main conceptual categories emerged from the narratives of the participants: (a) relational situations that echo the betrayal dynamic and (b) strategies to cope with relational situations involving betrayal: protection, reparation, and the use of both strategies, which leads to ambivalence. Findings highlight the importance of addressing the traumagenic dynamic of betrayal in interventions with sexually abuse youths, given their likelihood to experience betrayal in the context of romantic relationships and their increased risk of revictimization.